The ethical design of digital products and services as an instrument to safeguard the dignity, freedom and mental health of users (Justicia &Derecho, 2025)
This paper examines some addictive design strategies used by entertainment or interpersonal communication platforms and their impact on the dignity, freedom and mental health of users. In response to this, the argument is based on the need to safeguard human dignity from the very design of these products and services, based on an initiative of the European Parliament aimed at studying the legal loopholes in the matter and generating legislative proposals against addictive design.
Keywords: Ethical design; addictive design; digital products; human dignity